Evaluasi Pengaruh Fasilitas Halte Transjakarta Terhadap Tingkat Kepuasan Penumpang Menggunakan Analisis SPSS - Ferdinald, Donald Junius; Siregar, Herwin; Mubarok, Abdul; Manurung , Edison H. (International Journal Labs, 2025)
Public transportation plays a crucial role in urban mobility, especially in Jakarta, which faces various challenges such as traffic congestion and air pollution. TransJakarta, as a Bus Rapid Transit (BRT) system, is expected to be a solution for improving public transportation efficiency. However, passenger satisfaction with TransJakarta services is still influenced by the quality of bus stop facilities. This study aims to evaluate the impact of bus stop facilities on passenger satisfaction at three locations: Dukuh Atas 1 Bus Stop, Kampung Rambutan Bus Stop, and CSW Bus Stop. This research employs a quantitative approach with a descriptive method. Data were collected through questionnaires distributed to 185 respondents using a purposive sampling technique. The analyzed variables include accessibility, facilities, comfort, and security of bus stops. Data analysis was conducted using SPSS software with linear regression techniques to identify the relationship between bus stop facilities and passenger satisfaction. The research results indicate that the level of passenger satisfaction with TransJakarta shelter facilities at Dukuh Atas 1, Kampung Rambutan, and CSW shelters is generally in the fairly good category. Although some facilities have met passenger needs, several aspects, such as waiting area comfort, seat availability, and supporting facilities, still need improvement. Regression test results show that shelter facilities (X2) with a regression coefficient of 0.494 (t-value 5.687; significance 0.000) and shelter security (X3) with a regression coefficient of 0.473 (t-value 5.404; significance 0.000) have a significant impact on passenger satisfaction. Meanwhile, shelter accessibility (X1) and shelter comfort (X4) do not have a significant effect, with significance values of 0.569 and 0.780, respectively. To improve satisfaction, it is recommended to enhance shelter facilities such as ergonomic seating and real-time digital information boards, strengthen security systems with CCTV and optimal lighting, and conduct regular facility maintenance.